Nanoscale patterning of self-assembled monolayers using DNA nanostructure templates. Issue 8 (14th December 2015) - Surwade, S. P.; Zhou, F.; Li, Z.; Powell, A.; O'Donnell, C.; Liu, H.
Abstract : We describe a method to pattern arbitrary-shaped silane self-assembled monolayers (SAMs) with nm scale resolution using DNA nanostructures as templates. Abstract : We describe a method to pattern arbitrary-shaped silane self-assembled monolayers (SAMs) with nm scale resolution using DNA nanostructures as templates. The DNA nanostructures assembled on a silicon substrate act as a soft-mask to negatively pattern SAMs. Mixed SAMs can be prepared by back filling the negative tone patterns with a different silane.